Combining topography and peptide to inhibit algae attachment: Preparation of peptide‐modified microstructured surfaces. (17th August 2021) - Cao, Pan; Liu, De; Liu, Yuhan; Zhang, Yan; Yuan, Chengqing; Zhang, Chao
Abstract : Marine facilities and ships are easily plagued by biofouling. Synergistic surfaces combining surface reactive ion etching and peptide modification were designed and prepared to tackle surface biofouling. Six microstructural surfaces were first designed and machined based on the contact point theory; the synergistic surfaces were then prepared by peptide modification. Laser confocal scanning microscope (LCSM), scanning electron microscopy (SEM), contact angle measurement, and X‐ray photoelectron spectroscopy (XPS) were utilized to analyze the surface morphology and surface chemical properties; the results demonstrated that six synergistic surfaces were prepared successfully with 0.8‐μm depth, surface contact angle increased from 75° to 116.99°, and the surface chemical compositions were also changed significantly due to peptide modification. Antibiofilm assays showed that surface modification and surface topology could slightly reduce the formation of biofilm. While the synergistic surfaces possess strong anti‐algal performance, and anti‐ Chlorella pyrenoidosa ( C. pyrenoidosa ) and anti‐ Phaeodactylum tricornutum ( P. tricornutum ) rates reached 78.56% and 87.80%, respectively after 7‐day immersion in artificial seawater. Compared with the single surface treatment method, the antifouling performance of the synergetic surfaces were stronger. This strategy demonstrated a realistic paradigm for the further improving surface antifouling performance in a green method.